Assessment of Mothers' Knowledge upon their Children with Enzyme Deficiency (G6PD) in Pediatric Teaching Hospital at AL-Hilla City/Iraq - Abdul Mahdi. A. Hasan (Journal of Global Pharma Technology, 2018)
Aims of the study to identify knowledge of mother's toward their children with G6pd. And to find out demographic characteristic of mother's children with G6pd like age level of education. Methodology: 1 .design of the study: descriptive study of mother and child. 2. Setting of the study: the study was carried out of maternal and child Babylon hospital. 3. Time of the study: the study period extended from 20 november2016 to 12 January 2017. Results: Glucose-6-phosphate dehydrogenase (G6PD) regulates production of the reduced form of Nicotinamide adenine dinucleotide phosphate (NADPH) through the pentose phosphate pathway. G6PD may therefore affect superoxide anion production via vascular NADPH oxidase, which is key in mediating the vascular response to angiotensin II (Ang II). We determined the hypertensive and vascular hypertrophic response to Ang II in G6PD-deficient mice. Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common human enzymopathy and in Babylon Iraq, is a significant cause of infection- and drug-induced hemolysis and neonatal jaundice. Our goals were to determine the prevalence of G6PD deficiency among Babylon children of different ethnic backgrounds and to identify predictors of G6PD deficiency by analyzing vital signs and hematocrit and by asking screening questions about symptoms of hemolysis. We studied 200 children (100 males and 100 females) aged 1 month to 15 years. We found that the overall prevalence of G6PD deficiency was 15.3% (38.5% in males, 61.5% in females). Mean oxygen saturation, heart rate and hematocrit were not significantly different in G6PD deficient and G6PD sufficient children In conclusion; we determined the prevalence of G6PD deficiency in Nigerian sub-populations. The odds of G6PD deficiency were decreased in Igbo children compared to Yoruba children. There was no association between vital parameters or hematocrit and G6PD deficiency. We found that a history of scleral icterus may increase the odds of G6PD deficiency, but we did not exclude other common causes of icterus such as sickle cell disease or malarial infection. Recommendations Molecular screening for all deficient patient admitted to pediatric hospitals due to hemolytic crises.so establishing and conducting educational awareness programs for G6PD deficiency especially among mother's .and specific clinical follow up program for the deficient children and their families and establishing nationwide program of newborn screening for G6PD deficiency.Keywords: Mother, Knowledge, Effect, Glucose 6 phosphate deficiencies, School age.